2015
DOI: 10.1080/02772248.2015.1070160
|View full text |Cite
|
Sign up to set email alerts
|

Effect of repeated oral administration of bifenthrin antioxidant status and acetylcholinesterase activity in brain of rats

Abstract: The oxidative-stress-inducing potential of the pyrethroid, bifenthrin, in the brain of rats was evaluated following daily oral administration of 5.8 mg/kg body weight. Lipid peroxidation in the brain was increased, while the activities of superoxide dismutase, catalase, glutathione peroxidase, and glutathione S-transferase decreased. The activity of acetylcholinesterase (AChE) in erythrocytes and brain also decreased. Bifenthrin induces severe oxidative stress in brain, and inhibits brain and erythrocyte AChE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…These features are considered to be the reasons for the high neuroprotective activity observed above [29,34]. Since the fermentation extracts and β-carotene showed high neuroprotective activity in the above results, it is possible to expect the correlation between the activities against oxidative stress and the neuroprotective activity, which can derive a neuroprotective mechanism that is associated with antioxidant activities, whose mechanism was also proposed in other works [25,35,36]. To confirm this hypothesis, the reduction of ROS production was also observed in this work, because this treatment induces oxidative damage, Ca 2+ ions induce ROS activity, and Glutathione (GSH) inhibits ROS formation [36].…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…These features are considered to be the reasons for the high neuroprotective activity observed above [29,34]. Since the fermentation extracts and β-carotene showed high neuroprotective activity in the above results, it is possible to expect the correlation between the activities against oxidative stress and the neuroprotective activity, which can derive a neuroprotective mechanism that is associated with antioxidant activities, whose mechanism was also proposed in other works [25,35,36]. To confirm this hypothesis, the reduction of ROS production was also observed in this work, because this treatment induces oxidative damage, Ca 2+ ions induce ROS activity, and Glutathione (GSH) inhibits ROS formation [36].…”
Section: Discussionsupporting
confidence: 65%
“…The enzyme activity of glutathione was measured at 412 nm after adding 1 mM NADPH to 1.0 mL of a solution containing 100 µg of the sample, 0.1 M sodium phosphate buffer (pH 7.6), 1 mM EDTA, 1 mM GSSG and 0.6 mM 5,5 -dithiobis-2-nitrobenzoic acid (DTNB). The activity of glutathione reductase was also measured by calculating the ratio of the production of 2-nitro-3-thiobenzoic acid from DTNB during the reduction of glutathione [25,26].…”
Section: Measurement Of Glutathione Peroxidase and Glutathione Reductmentioning
confidence: 99%
“…Noeman et al [35] and Dar et al [36] also observed in their respective studies that the MDA cross linking and oxidative damage can also cause the inhibition of AChE enzyme due to the different pollutants like insecticides. The level of AChE in the brain, blood and erythrocytes was decreased with the increasing dose of bifenthrin, it indicates that bifenthrin has a higher tendency to inhibit AChE.…”
Section: Discussionmentioning
confidence: 95%
“…Rats treated with LD 50 of permethrin and cypermethrin showed elevated activity of AChE in specific regions of the brain and inhibited activity in other regions [17]. Some reports show that bifenthrin treatment induced a decrease of AChE activity [18], while others show no effect of this pyrethroid on AChE activity in rats [19]. Xylene was reported to cause changes in neuronal cells, such as increased levels of dopamine or catecholamine and reduced axonal transport in rat brains [20][21].…”
Section: Discussionmentioning
confidence: 99%